Metamorfosis Bayang: Revitalisasi Semesta Wayang dalam Praktik Seni Rupa Kontemporer dan Transmedia Indonesia - Wiratno, Tri Aru (Jurnal SeniRupa Warna, 2026)
This article explores the representation of the wayang universe within Indonesia's contemporary visual culture landscape through a critical revitalization approach. Wayang is no longer viewed as a static artifact of tradition, but rather as a dynamic sign system that continuously mutates in contemporary fine arts and transmedia narratives. Utilizing a descriptive qualitative method along with an in-depth literature study, this research reveals that current revitalization practices occur through visual deconstruction and massive digital technology adaptation.The findings indicate that the wayang universe serves as an elastic bridge for national identity, capable of adapting to new media—such as kinetic installations, films, and digital platforms—without losing its philosophical essence. The novelty of this study lies in identifying the concept of "Techno-Tradition," wherein the esoteric values of wayang are encrypted into modern algorithms. This phenomenon reinforces wayang’s position in global fine arts discourse, not merely as a heritage of the past, but as a form of local modernity that is responsive to global issues such as power politics, ecological crises, and identity disruption in the cyber era. The study concludes that the sustainability of wayang relies on a revitalization methodology that balances traditional aesthetic standards (pakem) with the flexibility of new media, positioning it as a competitive cultural capital in the international creative market.